Therapist and Client Interactions in Motivational Interviewing for Social Anxiety Disorder. Issue 7 (31st October 2016) - Romano, Mia; Arambasic, Jelena; Peters, Lorna
Abstract : Objective: The aim of the present study is to assess the bidirectional associations between therapist and client speech during a treatment based on motivational interviewing (MI) for social anxiety disorder. Method: Participants were 85 adults diagnosed with social anxiety who received MI prior to entering cognitive behavioral therapy. MI sessions were sequentially coded using the Motivational Interviewing Skill Code 2.5. Results: Therapist MI‐consistent behaviors, including open questions as well as positive and negative reflections, were more likely to be followed by client change exploration (change talk and counter‐change talk). Therapist MI‐inconsistent behaviors were more likely to precede client neutral language. Client language was also found to influence therapist likelihood of responding in an MI‐consistent manner. Conclusion: The findings support the first step of the MI causal model in the context of social anxiety and direct future research into the effect of therapist and client behaviors on MI treatment outcome.